Frequency-diverse MIMO metasurface antenna for computational imaging with aperture rotation technique - Wang, Tong; Han, Jiaqi; Ma, Xiangjin; Liu, Haixia; Li, Long (Frontiers in Materials, 2023)
Metasurface antennas have been proposed for computational imaging (CI) systems, which can reconstruct images without using mechanical scanning or large antenna arrays. In the CI system based on metasurface antennas, a variety of different radiation fields, which can be applied to sample the objects, are generated by exciting different frequency points in broadband. According to the compressed sensing theory, the imaging performance of the system is limited by the diversity of frequency-diversity radiation modes. In general, it is difficult to achieve rich radiation modes,therefore, a special design of metasurface aperture is required. In this paper, we propose a frequency-diversity MIMO metasurface antenna that consists of 2 × 2 sub-apertures with randomly distributed surface impedance. By employing the aperture rotation technique (ART) which rotates the MIMO metasurface antenna around the panel axis, the pseudo-randomness of the radiation fields is utilized, and the diversity of the radiation field is improved on the premise of ensuring the relatively low complexity of the system. The ART significantly improves the measurement richness at the cost of increasing the measurement time. The performance of the proposed method is evaluated. The simulated and experimental results verify the effectiveness of the proposed method in reconstructing high-quality images.